Functional traits and symbiotic associations of geoxyles and trees explain the dominance of detarioid legumes in miombo ecosystems. Issue 2 (21st February 2021) - Gomes, Amândio L.; Revermann, Rasmus; Meller, Paulina; Gonçalves, Francisco M. P.; Aidar, Marcos P. M.; Lages, Fernanda; Finckh, Manfred
Summary: The miombo region in Africa is covered by a mosaic of woodlands and geoxylic grasslands and is subject to disturbances such as fires, frost and drought, and low nutrient availability. The dominance of Fabaceae Detarioideae species in miombo ecosystems is remarkable but little understood. We therefore compared plant functional traits (PFTs) of common woody species of the Angolan plateau, grouped by life form (trees, geoxyles), lineage (Fabaceae: Detarioideae, non‐Detarioideae) and symbiont association (ectomycorrhiza, rhizobia). PFTs reflect group‐specific adaptations to prevalent environmental conditions. To analyse the impact of environmental drivers, we selected PFTs reflecting ecophysiological aspects of leaf morphology, nutrient content and water transport. Traits were measured following standardized protocols. We found differences in key PFTs between trees and geoxyles reflecting both life form‐specific adaptations to environmental conditions and lineage‐specific strategies to cope with environmental stresses. We interpret higher leaf thickness and higher wood density of geoxyles as responses to harsher open environments. Fabaceae in general and ectomycorrhizal species showed better nutrient status. Symbiotic associations of detarioid legumes with ectomycorrhiza show specific advantages for phosphorous uptake as compared to Rhizobia‐associated Fabaceae and to non‐Fabaceae and thus may be crucial for the stunning dominance of Detarioideae in miombo landscapes.